In vitro Study: The Potential for Papain Production from Papaya Leaf Callus - I. Indarwati; Dwie Retna Suryaningsih; Sri Arijanti; Alviana Wahyu Qurotin (Universitas Sembilanbelas November Kolaka, 2021)
Normally papaya plant can create sap white when tapped or in hur. Sap white it very well may be created on the entirety of its parts like natural product, blossoms and leaves petiole. Papain is a proteolytic catalyst that is created by secluding papaya sap. Papain is valuable as a breakdown of protein particles, and is regularly utilized by numerous individuals in different kinds of mechanical fields. The advantage of papain are so assorted thatb it has been broadly need for improvement perposes in industry, medication and creature feed. Papain creation can be developmentt with Biotechnology tissue culture .With improving the creation of callus plantled outgrowth leaves can expanded the cantaint of papain. The exploration goals were to decide the sorts of papaya assortments whose leaf callus could create the best papain. Realizing the papain content that can be created from three assortments of papaya leaves planted on MS and VW media. The exploration strategy utilized a totally randomized plan. Factor I was papaya assortments with 3 levels (California, Bangkok, and Gantung ). The subsequent factor is the sort of culture media (MS and VW). There are 6 mixes. Every treatment mix is rehashed multiple times with 10 test tests. The outcomes appeared; (1) There was a cooperation between the treatment of the concentrate source from the leaves of 3 sorts of Papaya assortments and the utilization of MS and VW media on callus amount and callus quality boundaries. (2 The amount and nature of callus on MS media was better compared to in VW media. (3) Callus of leaves California assortment produce Papain best than Bangkok and Gantung Variety. (3) Research result show that : all callus produces papain. The callus papaya all assortment containing papain range 11,86 % - 19,50 %.. The best found in treatment papain M1V1 ( MS Media - California (19,50 %); M2V1 (VW Media – California) 18,06 % papain content